Is it possible to determine the economic impact of jellyfish outbreaks on fisheries? A Case Study – Slovenia - NASTAV, B.; MALEJ, M.; MALEJ Jr., A.; MALEJ, A. (Mediterranean Marine Science, 2013)
The interdependence between the economy and the environment is becoming a fact of increasing importance. Productive coastal areas have been recognised as one of the most valuable ecosystems from an ecological and socio-economic point of view. In this paper we focus on the massive presence of jellyfish in the northern Adriatic and their effect on the Slovenian economy. Our results indicate that high jellyfish abundance in 2004 resulted in a reduction of fish catch, value added, gross income, and employment in the fishing industry. Moreover, the government and the EU have acknowledged the impact of jellyfish on the fishing industry by allocating financial help to the fishermen involved. We attempted to assess other factors influencing the fishing industry but none were statistically significant. The input-output analysis has not revealed a significant impact on the entire Slovenian economy presumably due to the small contribution of the fishing industry to Slovenian GDP. Our work is a first attempt to relate ecological changes such as jellyfish outbreaks in the northern Adriatic to the wider economy and we suggest that such a methodology can be applied to other countries/regions and to other natural phenomena affecting the economy.